Results of prostate cancer screening in non-symptomatic men - Antonopoulos, I. M.; Pompeo, A. C. L.; El Hayek, O. R.; Sarkis, A. S.; Alfer, W.; Arap, S. (My University, 2001)
Objectives: To verify prostate cancer prevalence in non-symptomatic men between 50 and 70 years old as well as cancer characteristics. Material and Methods: 2815 non-symptomatic men had total PSA and digital rectal examination performed between March 1998 and April 1998. Racial distribution was: 2331 Caucasians (83.9%), 373 Blacks (13.4%) and 75 Asiatic (2.7%). PSA was normal in 2554 (91.4%), 4 to 10 in 177 (6.3%) and greater than 10 in 64 (2.3%). DRE was normal in 2419 (86.3%), suspicious in 347 (12.4%) and characteristic for cancer in 37 (1.3%). Men with abnormal DRE and/or PSA had transrectal prostate biopsy indicated. Results: 461 biopsies were done and 78 tumors was detected (prevalence = 2.8%). Prevalence was progressively higher with age (p < 0.001), PSA level (p < 0.0001) and DRE findings (p = 0.0216). Cancer prevalence in Blacks was 1.65 times higher than in Caucasians (p > 0.05) and 94.9% of detected tumors were moderately or poorly differentiated. Sensibility, specificity, positive predictive value, negative predictive value and total accuracy for PSA were respectively: 66.6%; 89.7%; 51.7%; 94.2% and 86.5%. For DRE, the respective values were: 49.1%; 79.4%; 50.9%; 78.3% and 70.3%. Conclusions: prostate cancer prevalence in the studied population (2.8%) was similar to that of other countries populations. Cancer prevalence in blacks was 1.65 times higher than in Caucasians (difference was not statistically significant). Cancer prevalence becomes higher with aging. The association of DRE and PSA is of paramount importance for cancer diagnosis. The great majority of detected tumors (94.9%) was moderately and poorly differentiated. Brazil probably needs regional studies to better characterize prostate cancer epidemiology due to population heterogeneity.
Keywords: Prostate; Prostate-specific antigen; Prostatic neoplasm; Screening; prostate specific antigen; accuracy; adult; age; aged; aging; Asian; Brazil; cancer diagnosis; cancer epidemiology; cancer screening; Caucasian; controlled study; human; major clinical study; male; negro; palpation; population; prediction; prevalence; prostate biopsy; prostate cancer; race difference; sensitivity and sensibility; sensitivity and specificity; symptomatology; tumor differentiation